Migraine with aura after clopidogrel withdrawal: evidence of inflammation as a migraine trigger? – Case report - Folchini, Caroline Mensor; Santos, Paulo Sergio Faro; Giraldes, Jessica; Machado, Amanda Batista; Kowacs, Pedro André (Headache Medicine, 2022)
This article presents the case of a PFO (patent foramen ovale) closure patient with double antiplatelet therapy in whom aspirin was discontinued before clopidogrel and that, at clopidogrel withdrawal, presented “de novo” migraine with visual aura attacks. Migraines with aura associated with atrial right-to-left shunts (PFO and other atrial septal defects) are attributed to the arrival of vasoactive substances in the brain, since not cleared by the lungs. In this case, discontinuation of clopidogrel one year after PFO closure induced “de novo” migraine with aura. Conclusion Rather than confirming the prophylactic effects of clopidogrel for migraine with aura, its triggering at clopidogrel withdrawal is more likely related to a proinflammatory effect of discontinuing clopidogrel. This proinflammatory effect has been described in cardiological research, and reinforces that patients receiving dual antiplatelet therapy (clopidogrel and aspirin) should always have clopidogrel discontinued before aspirin in order to avoid proinflammatory or pro-thrombotic events.